2001
DOI: 10.1002/eat.1046
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal depression, eating, exercise, and vomiting before and during pregnancy

Abstract: Postnatal distress is associated with body weight and shape concerns, with disordered eating before and during pregnancy, and with vomiting during pregnancy. The protective role of low-intensity exercise during early pregnancy needs to be explored. Women with eating disorders should be considered at risk for postnatal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 12 publications
3
55
1
4
Order By: Relevance
“…The EPDS has been found to be more effective than general depression measures in identifying PPD symptoms. 52,53 To our knowledge, only one previous study 34 has used the EPDS to evaluate the association between eating disorder diagnoses and PPD. However, Abraham et al 34 only assessed PPD in the week after childbirth, a time when many women are still experiencing the relatively normative postpartum blues.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The EPDS has been found to be more effective than general depression measures in identifying PPD symptoms. 52,53 To our knowledge, only one previous study 34 has used the EPDS to evaluate the association between eating disorder diagnoses and PPD. However, Abraham et al 34 only assessed PPD in the week after childbirth, a time when many women are still experiencing the relatively normative postpartum blues.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…52,53 To our knowledge, only one previous study 34 has used the EPDS to evaluate the association between eating disorder diagnoses and PPD. However, Abraham et al 34 only assessed PPD in the week after childbirth, a time when many women are still experiencing the relatively normative postpartum blues. Finally, we examined the relevance of specific aspects of perfectionism to PPD, as previous investigations have indicated that particular forms of perfectionism are associated with eating disordered behavior.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…[66][67][68][69][70][71] Perinatal depression and eating disorder comorbidity Perinatal depression is common in women with an ED history. [10][11][12][13][14][15][16][17] 75 …”
mentioning
confidence: 99%
“…En nuestra paciente, el psiquiatra, de común acuerdo con el pediatra, indicó suspender la lactancia, además de prescribir fluoxetina, clonazepam y psicoterapia cognitivo-conductual, medidas con las que ha logrado una disminución significativa de su sintomatología depresivo-angustiosa y de sus conductas alimentarias alteradas. más aun, involucra la aparición de actitudes irresponsables de rechazo a la hija(o), con la emergencia de complicaciones médicas y/o psicopatológicas que conllevan inclusive un riesgo vital, tanto para la paciente como para la (el) lactante [43][44][45] . Según Micali y cols.…”
Section: Comentariounclassified